Pengolahan Jahe (Zingiber Officinale) Menjadi Puding Herbal Guna Meningkatkan Daya Tahan Tubuh Masyarakat di Desa Pulau Rengas - Nabillah, Syilsilia Rizkiani; Nursyamsyah, Ai; Purwanto, Hadi; M.S, Aliyah Faradina; Ghibran, Ghifahri (Jurnal Pengabdian UntukMu NegeRI, 2023)
Family medicinal plants or what are usually called TOGA are plants that can be cultivated in the home garden and have benefits as herbal medicines. Family medicinal plants can be an effort to prevent disease. The family medicinal plant used in this activity is ginger (Zingiber Officinale). Ginger is a plant from the Zingiberaceae tribe in the form of a rhizome which is very popular as a spice and medicinal ingredient. Because it is easy to find in traditional markets and is well known in the community. The activity was carried out in Pulau Rengas Village, Pangean District, Kuantan Singingi Regency, Riau. The aim of this activity is to provide education and encourage people to maintain and increase their immune system by consuming processed ginger products in the form of ginger pudding. Apart from that, it is hoped that the community can use their home gardens as a health aspect by planting family medicinal plants, namely ginger, in their yards. As a result, the people of Rengas Island Village can take advantage of the ginger planting and process it to make a product that is useful for increasing the body's immune system.